Characterizing macrophage diversity in colorectal malignancies through single-cell genomics - Zhao, Tingshuo; Luo, Yinyi; Sun, Yuanjie; Wei, Zhigang (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is one of the most common malignant tumors of the digestive tract, with increasing incidence and mortality rates, posing a significant burden on human health. Its progression relies on various mechanisms, among which the tumor microenvironment and tumor-associated macrophages (TAMs) have garnered increasing attention. Macrophage infiltration in various solid tumors is associated with poor prognosis and is linked to chemotherapy resistance in many cancers. These significant biological behaviors depend on the heterogeneity of macrophages. Tumor-promoting TAMs comprise subpopulations characterized by distinct markers and unique transcriptional profiles, rendering them potential targets for anticancer therapies through either depletion or reprogramming from a pro-tumoral to an anti-tumoral state. Single-cell RNA sequencing technology has significantly enhanced our research resolution, breaking the traditional simplistic definitions of macrophage subtypes and deepening our understanding of the diversity within TAMs. However, a unified elucidation of the nomenclature and molecular characteristics associated with this diversity remains lacking. In this review, we assess the application of conventional macrophage polarization subtypes in colorectal malignancies and explore several unique subtypes defined from a single-cell omics perspective in recent years, categorizing them based on their potential functions.